Laser cutting study of zirconium alloys for nuclear decommissioning - Jae Sung Shin; Joonsoo Ock; Sungyeol Choi (Nuclear Engineering and Technology)
We conducted laser cutting studies on zirconium alloys, specifically Zircaloy-2 and Zr-2.5%Nb alloy, which are used as constituent materials in the nuclear fuel channel of a pressurized heavy water reactor. The study measured the maximum cutting speed, amount of secondary emissions, and aerosol characteristics for each material using 10 mm thick plate specimens. The cutting performance of the zirconium alloys was similar to each other. At a laser power of 1–5 kW, the maximum cutting speed ranged from 750 to 1900 mm/min, and the amount of secondary emissions per length ranged from 32 to 53 g/m. Compared to 304 L stainless steel, the maximum cutting speed was 1.7–1.9 times higher, and the amount of secondary emissions was about 60–70 % of that of stainless steel. Analyzing the physical properties of aerosols, both zirconium alloys generated larger particles with a count median aerodynamic diameter of 0.25 μm, which is approximately 15–17 % larger than that of 304 L stainless steel.